From De-Humanization to the Flourishing Feast: A Study of Ecological Conversion by means of a Triple Colloquy with Pope Francis, Pope John Paul II, and Bernard Lonergan, S.J. - Krall, S.J., Christopher (Lumen et Vita, 2021)
This paper will first source Pope Francis’s notion of ecological conversion with Pope John Paul II’s writings that advocate for an awakening of humanity to a harmony with nature and one another. Second, using Bernard Lonergan’s notion of conversion as the foundational structure of religion, this paper will establish ecological conversion as an authentic movement into living more consciously as a member of the body of Christ. Finally, this paper will address how ecological conversion can reverse the destructive cycle of decline by drawing all of creation to the great heavenly feast.